VOCATIONAL GUIDANCE WORK AS AN INTEGRAL COMPONENT EDUCATIONAL ACTIVITIES OF PRIMARY SCHOOL STUDENTS - V.V. Berbetz (Academy of Cognitive and Natural Sciences, 2008)
In the article certainly essence, maintenance and task of professional orientation work, with students at basic school and methodical recommendations are offered in relation to the improvement of professional information work on the lessons o f labour studies.